1996
DOI: 10.1063/1.115937
|View full text |Cite
|
Sign up to set email alerts
|

Auger suppression in CdHgTe heterostructure diodes grown by molecular beam epitaxy using silver as acceptor dopant

Abstract: Negative differential resistance due to Auger suppression is demonstrated in CdHgTe diodes grown by molecular beam epitaxy (MBE) using silver as acceptor dopant. These devices require growth of relatively complicated heterostructures, and control of n- and p-type doping over a large range. For this reason, the use of silver as an acceptor in CdHgTe devices grown by MBE has been reexamined. The results show that the diffusion of silver at the growth temperature does not necessarily preclude the use of silver do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…There have been no systematic experimental studies of the Auger suppression through heterostructure engineering. Clear evidence of Auger suppression from heterobarrier–carrier interactions, however, has been reported widely in the literature. These experimental results unambiguously demonstrate a reduction in the dark current by realigning the heterostructures through alloy and doping compositions. Dark current is dominated by the thermal generation associated with the Auger mechanism in the narrow bandgap semiconductors .…”
Section: Resultsmentioning
confidence: 96%
“…There have been no systematic experimental studies of the Auger suppression through heterostructure engineering. Clear evidence of Auger suppression from heterobarrier–carrier interactions, however, has been reported widely in the literature. These experimental results unambiguously demonstrate a reduction in the dark current by realigning the heterostructures through alloy and doping compositions. Dark current is dominated by the thermal generation associated with the Auger mechanism in the narrow bandgap semiconductors .…”
Section: Resultsmentioning
confidence: 96%
“…Auger suppression translates into a negative differential resistance in the reverse-bias current-voltage (I-V) characteristics, which has been experimentally observed in devices grown by metalorganic vaporphase epitaxy (MOVPE) 2 and molecular-beam epitaxy (MBE) using silver as an acceptor dopant. 3 More recently, Wijewarnasuriya et al 4 reported Auger suppression in LWIR MBE-grown devices using arsenic as an acceptor dopant. Analytical 5 and numerical models 6,7 have been developed in order to study these devices.…”
Section: Introductionmentioning
confidence: 99%
“…In early work, 11 Auger suppression in MBEgrown HgCdTe heterostructure devices using silver (Ag) as a p-type dopant was demonstrated. However, the use of group V elements as p-type dopants in MBE has been studied extensively due to the larger atomic size of the group V elements, and hence, their lower diffusivity in HgCdTe.…”
Section: Introductionmentioning
confidence: 99%